2020
DOI: 10.12681/mms.22508
|View full text |Cite
|
Sign up to set email alerts
|

Filling gaps: closing the life cycle of the endangered Mediterranean limpet Patella ferruginea Gmelin, 1791 (Gastropoda, Patellidae)

Abstract: Several reproductive issues and the larval development of the ferruginous limpet, Patella ferruginea Gmelin, 1791, an endangered species endemic from the western Mediterranean Sea, were studied to fill gaps in the knowledge of its life cycle.Average diameter of mature oocytes was 141.83 μm and mean oocyte density in the ovary was 283,800 oocytes/gram. No significant correlations were found between both oocyte diameter or density and female shell length. Female fecundity (number of oocytes per gonad) was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
75
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(97 citation statements)
references
References 42 publications
12
75
2
Order By: Relevance
“…The early stages of larval development in Patella ordinaria appear in this study to be very similar to other related limpet species such as P. ferruginea (Espinosa et al, 2010;Guallart et al, 2020) or P. vulgata (Dodd, 1957;Wanninger et al, 1999) and slightly faster than those recorded in P. caerulea (Wanninger et al, 1999). In both cases, development times did not exceed 48 h, making these species very vulnerable to any environmental alteration to which they are subjected (Morgan, 1995;Guallart and Templado, 2012;Parker et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…The early stages of larval development in Patella ordinaria appear in this study to be very similar to other related limpet species such as P. ferruginea (Espinosa et al, 2010;Guallart et al, 2020) or P. vulgata (Dodd, 1957;Wanninger et al, 1999) and slightly faster than those recorded in P. caerulea (Wanninger et al, 1999). In both cases, development times did not exceed 48 h, making these species very vulnerable to any environmental alteration to which they are subjected (Morgan, 1995;Guallart and Templado, 2012;Parker et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that the activation is a time‐dependent process in which the pH influence requires a given time to be effective. For P. aspera , the optimal AT was between 3 and 4 h, which is a long AT since few studies reported activation times longer than one hour (Aquino De Souza et al., 2009; Guallart et al., 2020; Pérez et al., 2019), and usually no more than 10 min (Damen & Dictus, 1994; González‐Novoa, 2014; Hodgson et al., 2007; Pabst‐Fernández, 2015; Pérez et al., 2019; Wanninger et al., 1999). RAO decreases at pH 10 or higher, as reported in other limpet species (Aquino De Souza et al., 2009), probably due to the degradation of the cellular membranes (Aquino De Souza et al., 2009) and the damage of the oocytes (González‐Novoa, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled production of the species in aquaculture facilities provides a sustainable alternative to the exploitation of the natural resources and could be applied for restocking purposes. The aquaculture of limpets is a recent research field, so few bibliographical and methodological resources are available (Ferranti et al., 2018; Guallart, 2010; Guallart et al., 2020; Mau & Jha, 2018a), and zootechnical requirements are mostly unknown (Mau & Jha, 2018a). Most efforts on limpets aquaculture research have been focused on the acclimation of adult stocks (Hua & Ako, 2020), design of artificial diets (Hua & Ako, 2016; Mau & Jha, 2018b), reproduction in captivity (Aquino De Souza et al., 2009; Ferranti et al., 2018; Hodgson et al., 2007; Hua & Ako, 2020; Kay & Emlet, 2002; Mau et al., 2018), larviculture and settlement induction (Ferranti et al., 2018; Hua & Ako, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations